2015
DOI: 10.1177/0892705715614068
|View full text |Cite
|
Sign up to set email alerts
|

Comparing of melt blending and solution mixing methods on the physical properties of thermoplastic polyurethane/organoclay nanocomposite films

Abstract: In this study, microstructural features and physical properties of thermoplastic polyurethane (TPU)/organoclay nanocomposites films prepared via melt blending (MB) and solution mixing (SM) methods were investigated in detail. Amount of organoclay into the composition varied in the range of 2 and 8 wt%. Microstructural properties of samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) methods. It was found that the organoclay layers exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…The results showed that simple reactive melt blending may improve the tensile stress and dynamic modulus of SAN membranes and the dispersion of CNTs in SAN matrix. Ercan et al [88] compared the effects of melt blending and solution blending methods on the physical properties of thermoplastic polyurethane/nanoclay composite films; nanoclays exhibited a higher dispersion, exfoliated, and semi-exfoliated structures in the melting blending synthesized samples compared to those from the solution blending experiments. The melt blending method appeared to result in improvements in creep resistance, and the gas and water vapor permeability of polyurethane/nanoclay films.…”
Section: Melt-blending Methodsmentioning
confidence: 99%
“…The results showed that simple reactive melt blending may improve the tensile stress and dynamic modulus of SAN membranes and the dispersion of CNTs in SAN matrix. Ercan et al [88] compared the effects of melt blending and solution blending methods on the physical properties of thermoplastic polyurethane/nanoclay composite films; nanoclays exhibited a higher dispersion, exfoliated, and semi-exfoliated structures in the melting blending synthesized samples compared to those from the solution blending experiments. The melt blending method appeared to result in improvements in creep resistance, and the gas and water vapor permeability of polyurethane/nanoclay films.…”
Section: Melt-blending Methodsmentioning
confidence: 99%
“…ere are also techniques which are used in compounding the reinforcement into the polymer matrix without the moldings. Out of all the available techniques, melt blending is one of the easier and environmental friendly techniques for producing polymer composites [137]. Ibrahim et al experimented with kenaf fibers as reinforcement in PLA as a polymer matrix by the melt blending technique [138].…”
Section: Techniques For Compounding Polymer Matrix With Reinforcementmentioning
confidence: 99%
“…Polyurethane (PU)/clay systems are one of the current organic/inorganic nanocomposites being extensively studied . The main goal of such studies is the preparation of materials with targeted functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of such studies is the preparation of materials with targeted functional properties. The presence of clay in a PU matrix can positively influence gas transport , mechanical , thermal , tear , and anticorrosion properties of nanocomposites. PU/clay composites can also be used as scratch‐resistant , flame‐retardant or shape‐memory materials .…”
Section: Introductionmentioning
confidence: 99%